FUNGSI HUTAN ADAT RIMBO TUJUH DANAU DI DESA BULUH CINA KECAMATAN SIAK HULU KABUPATEN KAMPAR - P, Febri Angga Putra; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Buluh Cina Village, Siak Hulu, Kampar Regency with the aim to know the function of Adat Rimbo Tujuh Danau Forest. Some of the problems in this research are (1) What is the Social function of Adat Rimbo Tujuh Danau Forest for the villagers in Buluh Cina? (2) What is the economic function of Adat Rimbo Tujuh Danau Forest for the villagers in Buluh Cina? (3) What is the Culture function of Adat Rimbo Tujuh Danau Forest for the villagers in Buluh Cina? The title of this research is "The Function of Adat Rimbo Tujuh Danau Forest in Buluh Cina Village Siak Hulu, Kampar Regency". This research aimed to find out what are the Social, Economic, and Cultural functions of Adat Rimbo Tujuh Danau Forest for the villagers in Buluh Cina. This research was conducted by observing five people as research subjects who really know the function of Adat Rimbo Tujuh Danau Forest. The data of this research were collected by interview, observation, and documentation. The result of this research is the forest are sustainably preserved by the community of Buluh Cina because they have variety of natural resources. These indigenous forest have important existences to all living things because they have the benefits to make a living, as a nature balancing, the breeding ground of flora and fauna. The society of Buluh Cina upholds the custom and the culture in preserving the Adat Rimbo Tujuh Danau Forest remarkably.Keywords: Forest, Adat Rimbo Tujuh Danau forest, Buluh Cina Village